Teaming: how organizations learn, innovate, and compete in the knowled ge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and prom oting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those or ganizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible t eam-like entities. The pace of change and the fluidity of most work st ructures means that it's not really about creating effective teams any more, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encom pass are able to learn. The problem is teams, and other dynamic groups , don't learn naturally. Edmondson outlines the factors that prevent t hem from doing so, such as interpersonal fear, irrational beliefs abou t failure, groupthink, problematic power dynamics, and information hoa rding. With Teaming, leaders can shape these factors by encouraging re flection, creating psychological safety, and overcoming defensive inte rpersonal dynamics that inhibit the sharing of ideas. Further, they ca n use practical management strategies to help organizations realize th e benefits inherent in both success and failure. Presents a clear expl anation of practical management concepts for increasing learning capab ility for business results Introduces a framework that clarifies how l earning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it wel l Includes case-study research on Intermountain healthcare, Prudential , GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Child ren's Hospitals, among others Based on years of research, this book sh ows how leaders can make organizational learning happen by building te ams that learn.